TRENDS AND CHANGES IN TOURIST FLOW IN ROMANIA IN THE PERIOD 2009-2018 - Agatha POPESCU; Adelaida Cristina HONTUS; Mirela CARATUS-STANCIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper analyzed the tourist flow in Romania in order to identify the main trends and changes during the period 2009-2018 using the official empirical data and the specific indicators: tourist arrivals, overnight stays, average length of stay, monthly concentration rate, tourism intensity and residents' travels abroad. Romania has become year by year a more attractive tourist destination as the total arrivals reached 12.9 million in 2018, a double level than in 2009. The market is dominated by the Romanian visitors who accounted for 78% of arrivals. Hotels absorbed 9 million tourists, meaning 70 % of arrivals. More than 86 % foreigners prefer hotels. The overnight stays increased by 60% reaching 23.3 million in 2018, but the general trend is a decreasing one. Of the total overnight stays, 82 % belong to the Romanian tourists and 90 % are recorded in hotels. The length of stay is in general short about 2 days and with a tendency of decline. The most numerous arrivals are concentrated in August and July when the concentration rate is about 14-15 %. The occupancy rate increased, but it reached 22.18 % in 2018, the lowest level among the EU countries. In hotels, the occupancy rate reached 30 %. With 66 tourist/100 inhabitants and 54.13 per km2, Romania's tourism intensity is among the lowest in the EU. In 2018, the residents registered 21 million travels abroad, by 80 % more than in 2009 and with a tendency to grow. As a final conclusion, Romania's potential in tourism should be much better exploited, the demand/offer ratio should be balanced, tourist destinations should be more intensively promoted and service quality should be improved in order to grow the attractiveness of the country and tourist flow.